KARAKTERISTIK AKSEPTOR KONTRASEPSI INTRA UTERIN DEVISE POST PLACENTA DI PUSKESMAS WILAYAH KABUPATEN BANJARNEGARA TAHUN 2017 - Ratih Subekti; Lia Aria Ratmawati; Ratih Subekti; Lia Aria Ratmawati (Viva Medika, 2018)
The most ideal contraceptive for postpartum and breastfeeding mothers is not to suppress breast milk production such as Intra Uterine Device IUD, 3 month injections of contraception, minipil and condom. The IUD is a flexible plastic contraceptive device placed in the uterus, where as IUD post placenta is an IUD that is performed 10 minutes after birth or before uterine tailoring in the Section of Sesaria action. The purpose of this research is to know the characteristics of IUD post placenta respondents in Puskesmas of Banjarnegara Regency in 2017. This research uses descriptive research method with Cross Sectional approach. The instrument used is a table for recapitulation of contraceptive IUD post placenta acceptor data obtained from RM Puskesmas. The number of samples is 38 respondents. Data analysis using univariate analysis. The result of research is post placenta IUD acceptor age mostly in age group 20-35 years old that is 30 people (78.9%), education of post placenta IUD predominant are mostly Senior High School and Academic / PT that is 20 people (52.7%), parity acceptor post IUD placenta is mostly parity two that is as much as 20 people (52.6%) and the job of post placenta IUD acceptors are mostly IRT counted 35 people (91.1%). It is expected that health workers to improve family planning services through counseling and counseling to candidates KB post placenta IUD acceptors so that the number of acceptors can be improved. Key Words: post placenta IUD, age, education, parity, job